2013
DOI: 10.1016/j.oraloncology.2013.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Can extranodal spread in head and neck cancer be detected on MR imaging

Abstract: The MRI finding "infiltration of adjacent planes" may be high enough (100% in our study) to be used for treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…In the present study, the criteria used for declaring ENS were capsular contour irregularity and infiltration of adjacent planes. Lodder et al reported for these single criteria, using histopathological examination as reference standard, a sensitivity of 63% and 50% and a specificity of 93% and 100%, respectively. They found also that the largest diameter of >20 mm or >30 mm predicted ENS with a sensitivity of 70% and 50% and a specificity of 70% and 80%, respectively .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the criteria used for declaring ENS were capsular contour irregularity and infiltration of adjacent planes. Lodder et al reported for these single criteria, using histopathological examination as reference standard, a sensitivity of 63% and 50% and a specificity of 93% and 100%, respectively. They found also that the largest diameter of >20 mm or >30 mm predicted ENS with a sensitivity of 70% and 50% and a specificity of 70% and 80%, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…Lodder et al reported for these single criteria, using histopathological examination as reference standard, a sensitivity of 63% and 50% and a specificity of 93% and 100%, respectively. They found also that the largest diameter of >20 mm or >30 mm predicted ENS with a sensitivity of 70% and 50% and a specificity of 70% and 80%, respectively . We found a significant association between the presence of ENS on CT and/or MRI as a risk factor and the clinical risk factor of a lymph node of 6 cm or larger.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracapsular extension (ECE) was being evaluated on imaging, in case of doubt, a (super)selective neck dissection was done to confirm or exclude ECE.…”
Section: Methodsmentioning
confidence: 99%
“…Lodder et al [36] retrospectively studied the ability of MRI to detect ECS in 39 patients who had HNSCC that had been evaluated pre-operatively and subsequently underwent neck dissection. Using nodal measurements in conjunction with radiological and surgical designated neck nodal levels, a retrospective topographical correlation was performed.…”
Section: Extracapsular Spread Of Tumor (Ecs)mentioning
confidence: 99%